THE TRANSLATION OF ENGLISH NOUN PHRASE INTO INDONESIAN IN GARUDA INDONESIA MAGAZINE - Yuliani Paramita, Putu Dian; Mas Indrawati, Ni Luh Ketut; Seri Malini, Ni Luh Nyoman (JOURNAL OF LANGUAGE AND TRANSLATION STUDIES, 2016)
Abstract This study is concerned with translation field, especially on the shift in the process of English—Indonesian translation. It illustrates the types of shift that occurs in the Garuda Magazine. It is also aimed at discovering whether those English Noun Phrases are transferred into Noun Phrases in Indonesian. The principle of loss and gain of information in translation mostly occurs in the transfer of Source Language text to Target Language text. Regarding the research methodology, observation and a note taking technique are applied for the data collection and the theory used for the analysis is restricted to the shift proposed by Catford and the theory of loss and gain of information proposed by Nida.In relation to the above explanation, it is hoped that by recognizing shift and the theory of loss and gain information, the translator will be able to pinpoint and restate meaning more effectively due to it will be easier to get the intended meaning that is going to be translated.After analyzing the data, it was discovered that there were some shifts in translation occurring in the English noun phrases which were also translated into noun phrases in Indonesian as the target language. They were structure shift and intra-system shift. Meanwhile there were also shifts occurring in the translation of English noun phrase which were translated into non NP in the target language. According to the theory proposed by Catford about shift in translation, the shifts occured in this study was called class shift and unit shift. Based on the analysis, it was found that the theory of loss and gain of information proposed by Nida was also mostly applied in the process of transferring the meaning of the noun phrase of the source language text into the target language text.